Synopsis of the fossil Pristocerinae (Hymenoptera, Bethylidae), with description of two new genera and six species from Burmese, Taimyr, Baltic and Rovno ambers. (2nd September 2021) - Colombo, Wesley D.; Gobbi, Fernanda T.; Perkovsky, Evgeny E.; Azevedo, Celso O.
ABSTRACT: The flat wasps Bethylidae are a cosmopolitan family of aculeate ectoparasitoid of Coleoptera and Lepidoptera larvae. There are only 73 fossil species so far. Here, we provide a synopsis of the fossil pristocerine, which are those with strongly sexual dimorphism. Comments for all earlier described species are given. Two new genera and two species from Burmese and Taimyr ambers are described and illustrated, † Ekaterina volgatitan Colombo, Gobbi and Azevedo gen. et sp. nov. and † Uniceratops trex Colombo, Gobbi and Azevedo gen. et sp. nov. Four new species from Baltic and Rovno ambers are described and illustrated, † Cleistepyris allosaurus Colombo, Gobbi and Azevedo sp. nov., † Cleistepyris baryonyx Colombo, Gobbi and Azevedo sp. nov., † Pseudisobrachium megalosaurus Colombo, Gobbi and Azevedo sp. nov., † Pseudisobrachium stegosaurus Colombo, Gobbi and Azevedo sp. nov. The species Eleganesia electriphila (Cockerell) is transferred to Foenobethylus and has to be considered Foenobethylus electriphilus (Cockerell) comb. nov. The species Pseudisobrachium oligocenicum Théobald must be excluded from Bethylidae and has to be considered as Hymenoptera incertae sedis . The genus Cleistepyris is recorded for the Old World in the first time. A key for fossil pristocerine is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:03A13860-9AA3-4234-A3BE-5300ACC87BE5